Automatic loam soil machine / Muhammad Hariz Zulkanain, Muhammad Shafiq Mohd Afli and Mohamad Fahami Salleh - Zulkanain, Muhammad Hariz; Mohd Afli, Muhammad Shafiq; Salleh, Mohamad Fahami (2016)
Nowadays, the farmer has a problem to minimize the soil compaction due to the usage of the huge and heavy machine such as tractor. The farmer also has a problem to afford to pay a fuel bills due to consumption of fuel when we use tractor. Arduino Uno Board will be chosen to make a Automatic Loam Soil Machine for Final Year Project 1 (FYP 1). There are also problem occur when the farmer need to control the modem tractor manually that takes time and energy , so Automatic Loam Soil Machine will use ultrasonic sensor to detect the upcoming obstacle. In order to overcome these types of problem, exploration has been carried out with Automatic Loam Soil Machine was the answer to minimize the soil compaction. Other than that, Automatic Loam Soil Machine will always keep tract the condition of the soil. In return, the man energy can be reduced this is the reason and the important of why we are doing this project.